2014
DOI: 10.1152/ajpheart.00308.2013
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase inhibits oxygen consumption in collateral-dependent myocardium

Abstract: RJ. Inducible nitric oxide synthase inhibits oxygen consumption in collateral-dependent myocardium. Am J Physiol Heart Circ Physiol 306: H356 -H362, 2014. First published December 6, 2013 doi:10.1152/ajpheart.00308.2013.-Following coronary artery occlusion growth of collateral vessels can provide an effective blood supply to the dependent myocardium. The ischemia, which results in growth of collateral vessels, recruits an inflammatory response with expression of cytokines and growth factors, upregulation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It should be noted that the effect of NO on vascular growth 20 and myocardial blood flow 21 has been discussed controversially in the literature. Uncoupling of the eNOS enzyme can also aggravate oxidative stress.…”
Section: No Is a Mediator Of Exerciseinduced Arteriogenesismentioning
confidence: 99%
“…It should be noted that the effect of NO on vascular growth 20 and myocardial blood flow 21 has been discussed controversially in the literature. Uncoupling of the eNOS enzyme can also aggravate oxidative stress.…”
Section: No Is a Mediator Of Exerciseinduced Arteriogenesismentioning
confidence: 99%
“…Because ADMA inhibits NOS activity, this increase in DDAH1 expression may help preserve NO-dependent collateral vessel development and dilation 1,3 under conditions in which protein arginine methylation is increased. In support of the concept that increased DDAH1 expression increases eNOS activity and NO formation, a prior study from our lab found that inhibition of NOS activity with L-N G -Nitroarginine ( l -NNA) produced a greater decrease of blood flow in the collateral zone as compared to the remote zone or to normal hearts, 20 suggesting that vasodilation in the collateral zone is particularly dependent on NOS activity. In a previous study examining flow heterogeneity in normal canine hearts, Laussmann et al 29 reported that DDAH1 levels are high and ADMA levels are low in areas of low flow, compared to high flow regions.…”
Section: Discussionmentioning
confidence: 71%
“…We previously reported that iNOS expression and iNOS activity were increased in the collateral zone after 3 weeks of occlusions, and the coordinated expression of iNOS and eNOS acted to maintain collateral vasodilation to optimize the O 2 supply-demand relationship and protect the collateralized myocardium from ischemia. 20 Therefore, iNOS expression is important for both collateral vessel development and collateral vasodilation.…”
Section: Inos In the Midmyocardiummentioning
confidence: 99%